Pathogenic variants in the survival of motor neurons complex gene GEMIN5 cause cerebellar atrophy. Issue 6 (7th October 2021) - Saida, Ken; Tamaoki, Junya; Sasaki, Masayuki; Haniffa, Muzhirah; Koshimizu, Eriko; Sengoku, Toru; Maeda, Hiroki; Kikuchi, Masahiro; Yokoyama, Haruna; Sakamoto, Masamune; Iwama, Kazuhiro; Sekiguchi, Futoshi; et al.
Abstract: Cerebellar ataxia is a genetically heterogeneous disorder. GEMIN5 encoding an RNA‐binding protein of the survival of motor neuron complex, is essential for small nuclear ribonucleoprotein biogenesis, and it was recently reported that biallelic loss‐of‐function variants cause neurodevelopmental delay, hypotonia, and cerebellar ataxia. Here, whole‐exome analysis revealed compound heterozygous GEMIN5 variants in two individuals from our cohort of 162 patients with cerebellar atrophy/hypoplasia. Three novel truncating variants and one previously reported missense variant were identified: c.2196dupA, p.(Arg733Thrfs*6) and c.1831G > A, p.(Val611Met) in individual 1, and c.3913delG, p.(Ala1305Leufs*14) and c.4496dupA, p.(Tyr1499*) in individual 2. Western blotting analysis using lymphoblastoid cell lines derived from both affected individuals showed significantly reduced levels of GEMIN5 protein. Zebrafish model for null variants p.(Arg733Thrfs*6) and p.(Ala1305Leufs*14) exhibited complete lethality at 2 weeks and recapitulated a distinct dysplastic phenotype. The phenotypes of affected individuals and the zebrafish mutant models strongly suggest that biallelic loss‐of‐function variants in GEMIN5 cause cerebellar atrophy/hypoplasia. Abstract :